2017
DOI: 10.1521/soco.2017.35.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Race, Power, and Reflexive Gaze Following

Abstract: Observing shifts in others' eye gaze causes perceivers to shift their own attention in the same direction, and such gaze following has been regarded as reflexive. We hypothesized that effects of social hierarchy on reflexive gaze following are driven largely by power asymmetries. We used a standard gaze-cuing paradigm with 100 and 300 ms stimulus onset asynchronies. In Study 1, we compared gazers with a historically privileged social identity (European American/"White") to gazers with a historically underprivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 58 publications
5
32
0
Order By: Relevance
“…Although we did not register the ethnicity of our participants, study samples tested in our lab are typically composed of a majority of European decent. Under this assumption, our observations are congruent with gaze cuing studies showing a higher sensitivity to gaze cues of own-race 22 , 23 , 41 and high-status faces 42 , 43 . Due to the exploratory nature of this finding, the combined role of gaze and ethnicity on automatic imitation should be taken carefully until further replication.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although we did not register the ethnicity of our participants, study samples tested in our lab are typically composed of a majority of European decent. Under this assumption, our observations are congruent with gaze cuing studies showing a higher sensitivity to gaze cues of own-race 22 , 23 , 41 and high-status faces 42 , 43 . Due to the exploratory nature of this finding, the combined role of gaze and ethnicity on automatic imitation should be taken carefully until further replication.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the prespecified research questions, we explored if the influence of gaze on automatic imitation is conditional to other contextual factors. This question was motivated by earlier research showing that gaze cues are processed differently depending on the ethnicity and group membership of the observed face 18 , 22 , 23 . For example, in the study by Marsh et al 18 , in-group members with direct gaze elicited stronger compatibility effects than out-group members with direct gaze.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not register the ethnicity of our participants, study samples tested in our lab are typically composed of a majority of European decent. Under this assumption, our observations are congruent with gaze cuing studies showing a higher sensitivity to gaze cues of own-race (Collova et al, 2017;Dalmaso et al, 2015;Weisbuch et al, 2017) and high-status faces (Dalmaso et al, 2012;Liuzza et al, 2013). Due to the exploratory nature of this finding, the combined role of gaze and ethnicity on automatic imitation should be taken carefully until further replication.…”
Section: Why Did We Not Replicate the Effects Of Gaze On Automatic Imsupporting
confidence: 86%
“…In addition to the prespecified research questions, we explored if the influence of gaze on automatic imitation is conditional to other contextual factors. This question was motivated by earlier research showing that gaze cues are processed differently depending on the ethnicity and group membership of the observed face (Collova et al, 2017;Marsh et al, 2016;Weisbuch et al, 2017). For example, in the study by Marsh et al (2016), in-group members with direct gaze elicited stronger compatibility effects than out-group members with direct gaze.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that in humans gaze-mediated visual attention might also be more prevalent when viewing models who hold privileged status. Consistent with this, Weisbuch, Pauker, Lamer, and Adams ( under review ) recently found that White participants, who historically have held a privileged status in the U.S., only oriented attention to the gaze of White, not Black stimulus models, whereas Black participants oriented to the gaze of both groups. What is compelling about this finding is that a social group membership impacted what has long been considered an obligatory visual response, one not expected to be sensitive to top-down modulation.…”
Section: Social Visual Perceptionmentioning
confidence: 67%